Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.2307/2997301
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Variation in Alliaria petiolata (Brassicaceae) in Four Contrasting Habitats

Abstract: 0231). Demographic variation in Alliaria petiolata (Brassicaceae) in four contrasting habitats. J. Torrey Bot. Soc. 125:138-149. 1998-The expansion of Alliaria petiolata into a broad range of habitats in New Jersey was examined by comparing demographic and reproductive characteristics in four habitats that differed in availability of moisture and light. Plants behaved as strict biennials in all sites in all years. Survivorship, seed weight, and seed germination were lower in the drier habitats. The timing of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 25 publications
(34 reference statements)
4
83
2
Order By: Relevance
“…Abiotic factors may contribute to this variation, including nutrient status (Herrmann et al 2009), moisture (Byers and Quinn 1998, and landscape position (Burls and McClaugherty 2008). Earthworm densities ), powdery mildew infection (Ciola and Cipollini 2011), deer browsing ), and competition with native forest understory plants (Rebek andO'Neil 2006, Stinson et al 2006) have also been associated with garlic mustard invasions and may co-vary with its relative success in shaded sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abiotic factors may contribute to this variation, including nutrient status (Herrmann et al 2009), moisture (Byers and Quinn 1998, and landscape position (Burls and McClaugherty 2008). Earthworm densities ), powdery mildew infection (Ciola and Cipollini 2011), deer browsing ), and competition with native forest understory plants (Rebek andO'Neil 2006, Stinson et al 2006) have also been associated with garlic mustard invasions and may co-vary with its relative success in shaded sites.…”
Section: Discussionmentioning
confidence: 99%
“…Ecological evidence for population-level variation includes work on populations from lowland versus upland forests. Others have quantified site-specific demographic variation in seed maturation, survival, size, and allocation to (Byers and Quinn 1998), expression of phytochemical and physiological traits (Cipollini and Lieurance 2012, Lankau 2012b), and concurrent patterns of molecular and phenotypic variation that suggest evolutionary differences among geographically distinct populations (Bossdorf et al 2005, Mullarkey et al 2013). An avenue of future research is whether genetic composition and/or diversity differs at our sites from those where understory invasion has succeeded, and whether this is correlated with observed geographic and temporal environmental conditions.…”
Section: Additional Constraints To Invasionreduced Performance In Shadementioning
confidence: 99%
“…Rather, it appears that garlic mustard possesses a combination of traits, all slightly different from those of the surrounding native plants, which results in a highly successful species that is altering the composition and function of the native communities it invades. Garlic mustard exudes secondary compounds that interfere with native plant germination, growth, and ability to form symbiotic relationships Bossdorf 2004, Stinson et al 2006); it has escaped its natural enemies (Cavers et al 1979) and incurs little tissue loss to generalist herbivores (Nuzzo 2000, Blossey et al 2001; it competes successfully for resources (Meekins and McCarthy 1999); its phenology is substantially different from that of other native species; it is highly plastic in response to environmental variability (Byers and Quinn 1998); and it has high reproductive output (Cavers et al 1979). Moreover, if garlic mustard alters the soil environment in which it grows (e.g., by increasing nutrient supply or decreasing the abundance of mycorrhizal fungi in the soil), then the invasion by garlic mustard may have a positive feedback effect on its future success.…”
Section: Discussionmentioning
confidence: 99%
“…The rosette plant overwinters green under the snow and then bolts (produces a flowering stem) in March and April of the following year, growing at a rate of 1.9 centimeters per day (Cavers et al 1979, Anderson et al 1996. It produces flowers from April through July and fruits from June through September (Anderson et al 1996, Byers andQuinn 1998). Every viable second-year plant produces flowers, regardless of its size or site conditions (Susko and Lovett-Doust 1998), and plants can continue to produce flowers even after fruit production has started.…”
Section: Phenology and Reproduction As Mechanisms For Successmentioning
confidence: 99%
“…Typically, a ''site'' is limited in size to include an area relatively homogenous in climatic and edaphic properties (e.g., one farmer field). The properties associated with a given site are often highly correlated, especially with regard to their effects on plant performance; thus, it would seem site may often be sufficient to characterize current and future weed distributions (Andreasen et al 1991;Byers and Quinn 1998;Dale et al 1992;Dieleman et al 2000a). Davis et al (2005) found that the site effect explained 70 to 90% of the variation in common lambsquarters (Chenopodium album L.) and velvetleaf (Abutilon theophrasti Medik.)…”
mentioning
confidence: 99%